Determinants and Effects of Economic Fluctuations on the Contemporary Residential Real Estate Market - Główka, Gabriel (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
The market mechanism on the residential real estate market shows that the cyclicality of its development will not be eliminated due to its structural features. The residential real estate market is characterized by continuous tensions between rigid short-term supply and variable demand. Emerging imbalances may just disappear but they also may lead to crises.The results of research presented in the paper show that market fluctuations observed on the residential property market can be strongly exacerbated by the financial system, speculation and interventionism. When that happens, the risk of accumulation of this unfavorable phenomenon arises. Price bubbles may form as a result, causing the market to collapse and crisis to destabilise the entire economy. However, the analysis of these threats shows that the appropriate policy on housing demand can reduce the risk of a crisis. This constitutes an important challenge for public institutions and is especially important since the effects of the most recent global crisis have not been completely resolved. Moreover, the residential housing markets have recently observed disturbing price rises, suggesting that price bubbles could occur in the near future.